Understanding Criminogenic Risk Factors Among United States Military Veterans: An Updated Literature Review - Edwards, Emily R. (Criminal justice review, 2024)
Justice-involved veterans (JIVs) are a high-priority subgroup within the U.S. judicial system. In recent years, empirical research into the characteristics, needs, and outcomes of this veteran subgroup has developed rapidly. To allow research to better inform efforts to support JIVs, a systematic review was completed to organize existing literature on criminogenic risk within this population through the lens of the Risk-Need-Responsivity Model. Of the eight risk factors theorized by the Risk-Need-Responsivity Model, history of antisocial behavior and substance use had the most robust evidence as criminogenic risk factors for veteran justice involvement. Modest evidence was identified for antisocial personality, educational and occupational difficulties, and disruptions to family and marital relationships as risk factors. However, only limited evidence was identified for antisocial thinking, affiliation with antisocial peers, and lack of prosocial activities as risk factors due to these factors being relatively underassessed in research. Such patterns provide insight into potential interventions and supports for JIVs while also highlighting areas for continued research.